2022
DOI: 10.4081/gc.2022.10388
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional frailty in older people in general practitioners’ clinical practice: the SELFY-MPI SIGOT project

Abstract: The multidimensional prognostic index (MPI) is a comprehensive geriatric assessment (CGA) tool exploring the multiple domains of older subject. The knowledge and the diffusion of self-assessment tools for identifying frailty in general medicine is still limited. The aim of our study is to determine the prevalence of frailty using a multidimensional frailty screening tool (SELFY-MPI) in a cohort of older adults, belonging to the general practitioner’s (GPs) experience. In the frame of a national educational pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 25 publications
2
3
0
Order By: Relevance
“…Some elderly were living alone for more than 15 years, suggesting a potential social frailty. Similar findings had been observed in a study conducted by Pilotto A et al ,[ 16 ] (2022) which was carried out on general practitioners (GPs) in Italy, and suggested developing and diffusing comprehensive geriatric assessment in primary care settings. Polypharmacy and use of OTC herbal medications which were observed in this study warrant watchfulness for suspected adverse drug interactions in these patients.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Some elderly were living alone for more than 15 years, suggesting a potential social frailty. Similar findings had been observed in a study conducted by Pilotto A et al ,[ 16 ] (2022) which was carried out on general practitioners (GPs) in Italy, and suggested developing and diffusing comprehensive geriatric assessment in primary care settings. Polypharmacy and use of OTC herbal medications which were observed in this study warrant watchfulness for suspected adverse drug interactions in these patients.…”
Section: Discussionsupporting
confidence: 87%
“…observed that older people who were attending on GP’s ambulatories indicated that pre-frailty and frailty are common conditions that should be identified early to allow effective and personalized management based on the multi-dimensional profile of the individual elderly, suggesting the very key role of a primary/family physician in geriatric care. [ 16 ] The quality of primary care becomes important because of an advanced age, disease complexity, and multi-morbidity, resulting in hospitalization which can be improved by interventions targeting primary care[ 17 30 ] and use of screening tools such as STOPP/START and Beers criteria by the primary/family physician.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, to the best of our knowledge, SELFY-MPI is the only tool for self-reporting frailty available that cannot be considered only as a screening tool. As reported in other works, in older people, frailty, assessed using a multidimensional approach, has a prevalence of about 5%, and more importantly, prefrailty may affect about one person out of two [6,23,41]. In our study, we found a slightly lower prevalence of frailty and prefrailty, according to a multidimensional approach, probably because these older people were able to access the services for receiving vaccination against SARS-CoV-2; therefore, bedridden and more disabled, older participants were not included.…”
Section: Discussionsupporting
confidence: 55%
“…The sample size was calculated according to a work investigating the prevalence of multidimensional frailty with the SELFY-MPI among general practitioners in Italy [23]. In this regard, hypothesizing a prevalence of multidimensional frailty of 3.99%, a type I error of 5% and a power of 80%, 246 participants should be enrolled.…”
Section: Statistical Analysis and Sample Size Calculationmentioning
confidence: 99%